Epidemiological Study of Cardinal Signs and Reasonable Antibiotic Usage in FMD at Bagherpara Upazila in Jashore District - Sohadav Mazumder; Md Tareq Mussa; Md Atowar Rahman (Research in Agriculture Livestock and Fisheries, 2024)
Foot and mouth disease (FMD) is a viral disease that is epitheliotropic and transboundary, affecting cattle, buffalo, sheep, goats, and wild animals all over the world. Due to lower productivity and higher mortality in calves, this highly contagious disease causes significant economic loss. The study was conducted to identify clinical signs, management, complications, and prevalence of Foot and Mouth disease (FMD) in cattle for five months at Bagherpara Upazila, Jashore. A total of 66 cattle of both sexes were investigated clinically. The impact of season, breed, age, sex, and purpose of keeping cattle on disease incidence was investigated. In December, the prevalence of FMD was higher (27.27%). Crossbreds (71.21%) were discovered to be more vulnerable than local breeds (28.79%). Male and adult cattle were found to have a significantly higher prevalence of the disease than females and young cattle. Clinical observations of cattle affected by foot-and-mouth disease showed fever, salivation, erosive lesions in the oral mucosa and the interdigital region of the foot, and lameness. In complicated FMD cases, the antibacterial drug might be advised for clinical use to control secondary bacterial infection. Sulphadimidine, Ampicillin, and Oxytetracycline, as well as other supportive drugs, were used to treat the patient whereas the recovery rate was 90.91%, 77.27%, and 68.18%, respectively. Vol. 10, No. 3, December 2023: 327-334